Adaptasi Horor Turki ke Tradisi Drama Arab: Analisis Struktur dalam Drama Arab “SHIRREER” Teater OASE: Adaptation of Turkish Horror to Arabic Drama Tradition: Structural Analysis in the Arabic Drama “SHIRREER” by OASE Theatre - Shahira, Tasya Rifdha; Ekawati, Ekawati; Rokhim, Minatur; Nahdi, Sami Bin Nukman; Wardani, Yani'ah; Al Bahar, Ali Hasan (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
The drama Shirreer is an adaptation of the Turkish horror film Siccîn 1 into Arabic theater, which requires an in-depth study regarding the application of classical Arabic drama structures. This study aims to understand how the conventions of classical Arabic drama structures and their intrinsic elements are applied in the context of cross-cultural and media adaptations, particularly in the horror genre, which is thick with supernatural elements. This adaptation also shows how modern drama can combine tradition and innovation. The method employed is structural analysis, utilizing a qualitative descriptive approach. Primary data in the form of the Shirreer script is analyzed through the theoretical framework of the five stages of classical Arabic drama: Al-Muqaddimah, Al-Taqdim, Al-Tadhakhum, Al-Hall, and Al-Khatimah. This analysis also considers the distinctive characteristics of Arabic drama, including the use of the fus?a language, moral-religious themes, and the influence of classical Arabic rhetoric. The research was conducted through direct observation of the performance on December 20, 2024, at the Central Java Cultural Park and analysis of video recordings available on the UNS Oase Theater YouTube channel. The results of the analysis show that the three acts in the Shirreer script are mapped into the five stages of Arabic drama structure. Acts 0–1 serve as Al-Muqaddimah and Al-Taqdim, which introduce the characters and the conflict. Act II becomes Al-Tadhakhum through a supernatural confrontation. At the same time, Act III serves as Al-Hall and Al-Khatimah, presenting a tragic resolution and a profound moral message about the dangers of misusing spiritual power. The play successfully integrates the structure of classical Arabic drama into modern horror theater by maintaining important elements such as Quranic verses, fus?a diction, and religious themes, demonstrating the relevance of classical structure in a meaningful contemporary work.